Credit Markets with Ethical Banks and Motivated Borrowers - Barigozzi, Francesca; Tedeschi, Piero (Review of Finance, 2015)
Abstract We investigate the corporate social responsibility of banks. Lenders offer loans to standard and motivated borrowers who undertake either standard or ethical projects. Standard banks have no restriction on the types of projects for which they can provide a loan. Ethical banks, instead, commit to financing only ethical projects, which have social profitability but lower expected revenues. Motivated borrowers are keen to invest in ethical projects and to deal with ethical banks. When they are active, ethical banks increase social welfare because the matching of ethical lenders with motivated borrowers reduces the frictions caused by the agency issue.